Evaluating the Thymoquinone Content and Antioxidant Properties of Black Cumin (Nigella sativa L.) Seed Oil During Storage at Different Thermal Treatments - Grażyna Neunert; Wiktoria Kamińska; Joanna Nowak-Karnowska (Applied Sciences)
Black cumin seeds (Nigella sativa) and black cumin seed oil (BCSO) exhibit various pharmacological activities, most of which are attributed to the presence of thymoquinone (TQ). TQ, however, is characterized by low stability at elevated temperatures and instability in aqueous environments. In this study, the spectroscopic properties of TQ were used to monitor changes in TQ content in BCSO subjected to thermal exposure. Simultaneously, the influence of the presence of TQ on the antioxidant properties of this oil was determined. The used spectrofluorimetric and chromatographic method quantified the presence of TQ. The antiradical properties of the oil in different stages of thermal oxidation degradation were determined by the DPPH method. The measured antiradical activity of the oil, depending on the exposure conditions used, revealed the difference correlated with the content of the TQ. However, the presence in BCSO of other bioactive components, like phenols, had a more significant influence on its total antioxidant capacity. Furthermore, our study, for the first time, focused on the rise in TQ content in the oil during thermal storage, indicating a new method to enhance the TQ content in BCSO.